Agmatine as a potential therapeutic intervention in bipolar depression: the preclinical landscape. (3rd April 2019) - Watts, Devon; Pfaffenseller, Bianca; Wollenhaupt-Aguiar, Bianca; Paul Géa, Luiza; Cardoso, Taiane De Azevedo; Kapczinski, Flavio
ABSTRACT: Introduction : Present antidepressant treatments are only helpful in a quarter of patients with bipolar depression, and new strategies are warranted. Increasing evidence suggests that accelerated polyamine metabolism is associated with the pathophysiology of depression. Polyamines regulate stress responses, inflammation, and neuronal signaling in the central and enteric nervous system. Agmatine is a promising target of altered polyamine metabolism considering its unique ability to regulate intracellular polyamine content and neuroprotective effects. Areas covered : This review discusses the polyamine system and its relationship to the central and enteric nervous system, focusing on results from preclinical studies supporting the relationship between agmatine and the pathophysiology of depression. We also discussed the main mechanisms underlying the antidepressant and neuroprotective effects of agmatine. Expert opinion : Our review points out the possible relationship between polyamines and the pathophysiology of depression. It discusses the efficacy of agmatine in several models of depressive-like behaviour, and suggests that it may prove to be an efficacious adjunctive treatment in bipolar depression. Furthermore, it discusses a proposed pathway linking systemic inflammation, observed in a subset of bipolar disorder patients, to abnormal polyamine metabolism and associated changes in the epithelial gut barrier and blood-brain barrier.